Laser Surface Modification in Ti-xNb-yMo Alloys Prepared by Powder Metallurgy - Tendero, Inmaculada; Rossi, Mariana Correa [UNESP]; Viera, Mauricio; Amado, Jose Manuel; Tobar, Maria Jose; Vicente, Angel; Yanez, Armando; Amigo, Vicente (Mdpi, 2021)
The main objective was to study the effect of surface modification by laser on Ti-Nb-Mo powder metallurgical alloys to improve their mechano-chemical behavior and their application as a biomedical implant. The used powder mixtures were produced in an inert atmosphere. Uniaxial compaction took place at 600 MPa with high-vacuum sintering at 1250 degrees C for 3 h. The specimens for the three-point flexure test were prepared and their mechanical properties determined. Microstructural characterization was performed by scanning electron microscopy (SEM) and X-ray diffraction (XRD) to obtain the distribution of phases, porosity, size, and shape of the grains of each alloy. Corrosion behavior was evaluated by electrochemical tests using an artificial saliva electrolyte modified from Fusayama at 37 degrees C. Chemical characterization was completed by analyzing the ionic release by Inductively coupled plasma atomic emission spectroscopy (ICP-EOS) after immersion for 730 h in Fusayama solution modified with NaF at 37 degrees C to simulate a 20-year life span based on a daily 2-min cycle of three toothbrushes. Corrosion behavior confirmed promising possibilities for the biomedicine field. The surface porosity of the samples not submitted to surface treatment deteriorated properties against corrosion and ion release. The obtained phase was beta, with a low alpha-martensite percentage. The maximum resistance to bending was greater after surface fusion. Plastic deformations were above 7% under some conditions. Microhardness came close to 300 HV in heat-affected zone (HAZ) and 350 HV in fusion zone (FZ) (under the determined condition. The elastic modulus lowered by around 10%. The corrosion rate was lower in Ti-27Nb-8Mo and Ti-35Nb-6Mo. Niobium release was significant, but below the physiological limit.
Keywords: powder metallurgy; titanium; niobium; molybdenum; laser surface modification; laser melting